Measurement of isothermal (vapor+liquid) equilibria, (VLE) for binary (CH4+CO2) from T=(240.35 to 293.15) K and CO2 rich synthetic natural gas systems from T=(248.15 to 279.15) K - Nasir, Q. (Elsevier B.V., 2015)
Isothermal vapor-liquid equilibrium (VLE) data for methane (CH4) + carbon dioxide (CO2) binary system at temperature range of (240.35-293.15) K and synthetic carbon dioxide rich natural gas mixtures at temperature and pressure range of (248.15-279.15) K and (2.81-9.05) MPa were measured in sapphire type equilibrium cell apparatus. Thermodynamic modeling of experimental data was carried out with GERG2008-equation of state (EOS) and volume-translated Peng-Robinson equation of state (VTPR-EOS) using van der Waals (vdw1) mixing rule. For CH4 + CO2 system, the temperature dependent binary interaction parameters (kij) were tuned to measured VLE data, whereas, between CO2 with other hydrocarbons the value of kij=0 was assumed. Comparison between measured and prediction shows excellent agreement with overall lower deviations were obtained. Â© 2015 Elsevier B.V.